PENGEMBANGAN KOMUNITAS PEDESAAN DALAM PEMBANGUNAN MASYARAKAT PERTANIAN BERKELANJUTAN - Azwar Maulana (Department of Islamic Community Development, Faculty of Da'wah, State Islamic University (UIN) of Sultan Maulana Hasanuddin Banten, 2017)
Community Empowerment in Sustainable Agricultural Development (Study at Desa Asmorobangun, Kecamatan Puncu, Kabupaten Kediri). One of the duties of the nation is to provide the prosperity for the citizen through a development. The development is conducted by the government in order to reach the economic growth by utilizing all agriculture potentials and by organizing community development. In this study has yhe purpose is to know, describe and analyze the empowerment of the community in the village of Asmorobangun in sustainable agricultural development. Type of research is descriptive with qualitative approach data analysis uses Creswell’s model. Asmorobangun Village has a resource potential that is needed can apply sustainable agriculture development for community welfare. Through empowerment which involves several stages such as enlightenment, capacity building, and enforcement, hereby, the awareness, capacity, skill and strength of the community can be improved to exploit all potentials. The support given to the community in sustainable agriculture development is already not maximum. Despite this support, there are factors constraining community empowerment in sustainable agriculture development. These constraints may come from community, very few numbers of agriculture counselor, natural resource inadequacy, and also weather factor at Asmorobangun Village such that the empowerment process cannot be made maximum.